2008
DOI: 10.1111/j.1365-2834.2007.00843.x
|View full text |Cite
|
Sign up to set email alerts
|

Leadership role of Consultant Nurses working with Older People: a co-operative inquiry

Abstract: Within the context of the literature this area is under investigated. Understanding how leadership is reflected in the role of Consultant Nurses is complex as Consultant Nurses work across traditional interfaces and between different levels within organizations. Consultant Nurses have been 'challenged' to identify the 'difference' they are making; to do this it is important to understand how leadership (as one element) is reflected in a highly complex, multidimensional role and the links between leadership and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
43
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(43 citation statements)
references
References 25 publications
0
43
0
Order By: Relevance
“…Recent studies of effective development of consultant nurse roles in the UK provide evidence of improvement in service provision by a nationally representative sample (Coster et al, 2006), research leadership in practice (Chummun and Tiran, 2008), outreach work of critical care consultant nurses working beyond the boundary of the intensive care unit (Dawson and McEwan, 2006) and enhanced clinical practice and leadership skills of consultants in emergency nursing (Charters et al, 2005) and care of older people (Manley et al, 2008). An investigation of advanced nursing roles (n ¼ 855 of which 6% were consultant nurses) showed that self-ratings by consultant nurses of their own level of knowledge, skills and confidence in promoting evidence-based practice were higher than ratings reported by the other advanced practitioners of themselves on the same items (Gerrish et al, 2007).…”
Section: Introductionmentioning
confidence: 98%
“…Recent studies of effective development of consultant nurse roles in the UK provide evidence of improvement in service provision by a nationally representative sample (Coster et al, 2006), research leadership in practice (Chummun and Tiran, 2008), outreach work of critical care consultant nurses working beyond the boundary of the intensive care unit (Dawson and McEwan, 2006) and enhanced clinical practice and leadership skills of consultants in emergency nursing (Charters et al, 2005) and care of older people (Manley et al, 2008). An investigation of advanced nursing roles (n ¼ 855 of which 6% were consultant nurses) showed that self-ratings by consultant nurses of their own level of knowledge, skills and confidence in promoting evidence-based practice were higher than ratings reported by the other advanced practitioners of themselves on the same items (Gerrish et al, 2007).…”
Section: Introductionmentioning
confidence: 98%
“…The remaining three domains were also raised by participants when discussing consultant practice and are addressed in this section. Firstly, regarding leadership, Manley, Webster, Hale et al 22 reported that this aspect of the consultant role has ot ee e plo ed i depth, despite it ei g the ke e ha is fo a hie i g a d e eddi g t a sfo atio i p a ti e p. . Ca ti a d 'i ha ds23 (p.172) concur, arguing that leade ship u de pi s all of the othe fu tio s a d a ot e o side ed a dis ete phenomenon that we can analytically partition away from the other domains of practice.…”
Section: Four Domains Of Practicementioning
confidence: 99%
“…Information for instance is often adapted to the circumstances of a specific illness (Chin- Yen, Hung- Ru, Ing-Tiau, & Mei-Ling, 2008; Larsson, Hedelin, & Athlin, 2007) or to the individual patient's needs (Larsson et al, 2007). Other forms of situational-specific support, expressed by patients, include medical, psychological, or spiritual support in daily life (Harrefors, Sävenstedt, & Axelsson, 2008), but precisely what is included in these activities is not mentioned.…”
mentioning
confidence: 99%
“…Regardless of how support is described, the common denominator is that the activity is associated with good care outcomes (Björklund, Sarvimäki, & Berg, 2008; Chin-Yen et al, 2008; Dale et al, 2010; Drageset et al, 2009; Larsson et al, 2007; Winningham & Pike, 2006). However, the view of support and expected outcomes changes with the technical solutions brought about by the development in the health care of today.…”
mentioning
confidence: 99%
See 1 more Smart Citation